2018
DOI: 10.1142/s0217751x18501464
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric preheating

Abstract: We study the generation of the matter-antimatter asymmetry during bosonic preheating, focusing on the sources of the asymmetry. If the asymmetry appears in the multiplication factor of the resonant particle production, the matter-antimatter ratio will grow during preheating. On the other hand, if the asymmetry does not grow during preheating, one has to find out another reason. We consider several scenarios for the asymmetric preheating to distinguish the sources of the asymmetry. We also discuss a new baryoge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…In our future works, we are going to analyze in detail the conditions for asymmetric particle production [16,[29][30][31][32][33], using the ideas developed in this paper. Since baryogenesis requires B-violating interaction, and the interaction has to play a significant role in generating the asymmetry, the equations have to be multi-component (i.e, higher-order after decoupling).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In our future works, we are going to analyze in detail the conditions for asymmetric particle production [16,[29][30][31][32][33], using the ideas developed in this paper. Since baryogenesis requires B-violating interaction, and the interaction has to play a significant role in generating the asymmetry, the equations have to be multi-component (i.e, higher-order after decoupling).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In Ref. [16], we have shown that the "eigenstates" are preserving matter-antimatter asymmetry but they are mixed by the Berry connection. In this case, the phases in the Berry transformation are functions of ω φ , ǫ R , ω η and g. Therefore, in this model, one can expect that a time-dependent ω φ can generate matter-antimatter asymmetry, since it may change the phase parameter asθ i =ω φ (∂θ i /∂ω φ ).…”
Section: E Majorana Fermions For the Simplest Extensionmentioning
confidence: 99%
“…In Ref. [16], we showed a numerical calculation to show that the matter-antimatter asymmetry is generated in this model. Viewing with the "eigenstates"(Ψ E ), the Berry connection causes mixing between "eigenstates" accompanied by the CP phase, which is time dependent, to generate the interference between states.…”
Section: E Majorana Fermions For the Simplest Extensionmentioning
confidence: 99%
“…However, this naive speculation fails in the present model. One can calculate the behavior of |β| 2 (both numerically and analytically [19]) 1 to find that the evolution of |β h | 2 and |β g | 2 are identical in this case, resulting no asymmetry production. From this simple model, one can understand why μ = 0 (i.e, a time-dependent chemical potential) is needed for the asymmetry production.…”
Section: Introductionmentioning
confidence: 99%